From Mission to Church: Nature, Spatiality, and Catholicism in Kikwit (DRC) - Mick Feyaerts (Religions)
This study explores nature’s role in the spatial development of the local Roman Catholic Church in Kikwit, a mid-size city in the Democratic Republic of Congo. Founded as a mission station by Belgian Jesuits in 1912, the local Church has experienced a peculiar development over the last century. Roman Catholic communities seem grouped spatially according to their function. Communities with apostolic functions are located in the western part of the city, while contemplative and intellectual communities are concentrated in the eastern part. The dividing line appears to be the Kwilu River, which separates the lively commercial and residential center on the left bank from more rural municipalities on the right bank. This paper proposes that this spatial organization results from the interplay of multiple theologies of nature that led to different ways of engaging with the natural surroundings in the region. Moreover, the research suggests that the Catholic Church’s transformation from a missionary institution to a (more or less) independent Church in Kikwit relied heavily on nature because it allowed further development of both the apostolic and contemplative functions of the Church.